2016
DOI: 10.1155/2016/9367619
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Strength Development of Cement with Cenosphere and Silica Fume as Pozzolanic Replacement

Abstract: In the detailed study presented in this paper, an attempt was made to study the strength of cement when cenosphere (CS) and silica fume (SF) were used as replacement. Tests were carried out on mix with cenosphere as replacement for cement which has 12% of constant replacement of silica fume to the mass of cement, and this is made to stabilize the strength which was lost due to addition of cenosphere. From the test results, it was concluded that the strength loss of binder due to replacement of cenosphere can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…At present, the mixture ratio design of CPB refers to the relevant theory of concrete. Mitchell and Wong established the strength model by a large quantity of tests which show that the uniaxial compressive strength relates to the porosity, water cement ratio, and binder content [10][11][12][13]. Swan used "cementing agent coefficient" to estimate the uniaxial compressive strength which is related to the cementing agent content [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the mixture ratio design of CPB refers to the relevant theory of concrete. Mitchell and Wong established the strength model by a large quantity of tests which show that the uniaxial compressive strength relates to the porosity, water cement ratio, and binder content [10][11][12][13]. Swan used "cementing agent coefficient" to estimate the uniaxial compressive strength which is related to the cementing agent content [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Contradictory, [68] concluded that the addition of the cenosphere may decrease the strength so that it can be stabilized by the addition of silica fume. The property of nano-silica is to improve the interfacial transition zone in concrete, thereby obtaining an earlyage strength and attains a high compressive strength [69][70][71][72] stated that a slight decrease in strength of the mortar even at low density and low thermal conductivity of the cenosphere. 65] stated that strength loss in mortar can be strengthened by improving the interfacial property by using the cenosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, many investigations have been done by researchers to develop cost-effective concrete by blending industry by-products with cement [32][33][34]. Hence this study is envisaged to develop a new ecosustainable composite by using cenosphere as an alternative material for cement [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In a cement mantle, sufficient water should be incorporated to seal the voids present among solid particles [47][48][49][50][51][52][53][54][55]. If the voids are unfilled, the air may entrain into the concrete and that may result in strength reduction [56][57][58][59][60][61]. Hence in this research, the cenosphere content is varied for different W/C ratios to assess the mechanical and rheological properties.…”
Section: Introductionmentioning
confidence: 99%